Survivors narratives of intimate partner violence in Cape Town, South Africa: A life history approach - Chikwira, Rene (Department of Psychology, 2020)
Intimate partner violence (IPV) is a problem that is present and pervasive globally and in South Africa. In the South African context, IPV exists within a larger context of high levels of interpersonal violence and violence against women. Understanding the context in which IPV occurs from the perspective of survivors is important for informing effective intervention and prevention programs to counteract its effects. This study explores the life histories of South African women who have experienced IPV. Framed through the lens of intersectionality, it gauges the broader context within which IPV emerges and is sustained, and explores how experiences of IPV are shaped at the intersection of women’s identity markers of race, class and gender. This study is one of a few studies that have used life history methods with women to explore their life contexts and experiences of IPV. Purposive sampling was used to recruit a sample of 11 women based in a Cape Town women’s shelter for abused women and children. Two semi-structured qualitative life history interviews were conducted with each participant. The interviews were transcribed and analysed through thematic narrative analysis, where four noteworthy narrative themes emerged, namely An unsteady and violent beginning, No place called home: A search for belonging and survival, IPV: The unanticipated cost of love and belonging, and Normalisation of IPV experiences: The effects of withdrawal from support. The findings and their relation to existing literature as well as recommendations for future IPV research are discussed. One of the key findings of the study was that the childhood context of the participants was the first point of identifying intersectional oppression and marginalisation that may have shaped a vulnerability to the women’s later experiences of IPV. Another key finding was recognising the value that women place on love and belonging in the context of a difficult, violent and low socioeconomic childhood background, and how this could have an impact on the vulnerability of women to IPV. The use of a life history approach framed by intersectionality thus demonstrated significant benefits in tracking the contextual experiences of women who have experienced IPV. These benefits are of significance because they made it possible to identify points of intervention and prevention of IPV amongst marginalised South African women.